Identification of potential short linear motifs (SLiMs) in intrinsically disordered sequences of proteins by fast time-scale backbone dynamics - Snigdha Maiti; Soumya De (Journal of Magnetic Resonance Open, 2022)
Intrinsically disordered regions (IDRs) of proteins contain functionally important short linear motifs (SLiMs), which are composed of 3 to 10 residues. They are often crucial members in protein interaction networks (PINs) in various biological pathways. These short motifs are hard to identify and structurally characterize as very few techniques are amenable for studying IDRs. NMR spectroscopy has emerged as a powerful technique to study IDRs. Here we show that fast picosecond - nanosecond dynamics can be used to identify short rigid segments with significantly lower backbone flexibility compared to the rest of the IDR. Typically, the order parameter (S2) for the backbone amide (NH) bond vector is used to measure residue-wise rigidity. We show that the parameter R1R2/(1-NOE) can be conveniently used to measure residue-wise rigidity for disordered regions. Both the parameters S2 and R1R2/(1-NOE) identify the same rigid segments in the disordered region of the transcription factor SCR. Previously, we have shown that one of the identified rigid segments is indeed a SLiM and specifically interacts with a partner transcription factor. Furthermore, mutations were designed to introduce ionic interactions in a flexible linker connecting two rigid segments. Both the parameters S2 and R1R2/(1-NOE) detect increased rigidity of this flexible linker in the mutants, which was not detected from backbone chemical shifts. Also, no change in global hydrodynamics properties were observed from size exclusion chromatography. Thus, backbone dynamics is highly sensitive to residue-wise rigidity in disordered sequences, which can be conveniently determined from R1R2/(1-NOE) and can identify potential functional SLiMs.